Electrochemical Performance and Storage Mechanism of Ag2Mo2O7 Micro‐rods as the Anode Material for Lithium‐Ion Batteries. Issue 21 (27th March 2017) - Zhang, Meina; Gao, Yu; Chen, Nan; Ge, Xin; Chen, Hong; Wei, Yingjin; Du, Fei; Chen, Gang; Wang, Chunzhong
Abstract: Ag2 Mo2 O7 micro‐rods are prepared by one‐step hydrothermal method and their lithium electrochemical properties, as the anode for lithium‐ion batteries, are comprehensively studied in terms of galvanostatic charge–discharge cycling, cyclic voltammetry, and rate performance measurements. The electrode delivers a high reversible capacity of 825 mAh g −1 at a current density of 100 mA g −1 and a superior rate capability with a discharge capacity of 263 mAh g −1 under the high current density of 2 Ag −1 . The structural transition and phase evolution of Ag2 Mo2 O7 were investigated by using ex situ XRD and TEM. The Ag2 Mo2 O7 electrode is likely to be decomposed into amorphous molybdenum, Li2 O, and metallic silver based on the conversion reaction. Silver nanoparticles are not involved in the subsequent electrochemical cycles to form a homogeneous conducting network. Such in situ decomposition behavior provides an insight into the mechanism of the electrochemical reaction for the anode materials and would contribute to the design of new electrode materials in future. Abstract : Positive thinking : Ag2 Mo2 O7 micro‐rods were synthesized hydrothermally and then used in anodes for lithium‐ion batteries. The structural properties were monitored during charge–discharge to probe the mechanism of the electrochemical reaction, and to explain the high capacity and superior rate capability.